CLIFF-GRADS Science Collaboration Series 2020 - Special Session: National GHG Inventories - Glade, Olia (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
The 2020 CLIFF-GRADS Science Collaboration Series was developed to facilitate technical capability building, knowledge transfer and international collaboration for the CLIFF-GRADS Alumni. Particularly for the Round 3 CLIFF-GRADS whose research stays have been delayed due to the global Covid-19 Pandemic.